Pengaruh Kemampuan, Motivasi dan Kepemimpinan terhadap Kinerja Kader Posbindu PTM Kabupaten Banyuwangi - Kurnia Novita Putri; Christyana Sandra; Eri Witcahyo (Politeknik Negeri Jember, 2020)
The highest prevalence of malnutrition cases is in Gorontalo District which is 3.2% in 2018 and the highest public health center in the Tibawa area is 4.2% in cases of malnutrition and underfives carrying a red line are 4.7% and 2 toddlers do not gaining weight for 3 times in a row The results of growth and development monitoring were carried out at the posyandu until September 2018. This study aims to analyze the effect of nutrition assistance with media booklets to improve the knowledge and practices of hamlet heads in determining the nutritional status of children under five. The research method was quasi-experimental with pre -post, sample selection with a total sample of 77 respondents,37 interventions and 40 controls.The results showed that there were no significant differences in knowledge of the treatment and control groups before the pre intervention (p=0.857). There were significant differences in knowledge before and after the intervention group pos1 (p=0,000) and post2 (p=0,000) whereas in the post1 control group (p=0,000), there were significant differences at post2 (p=0.395) there were no significant differences. There was a difference after the intervention between the treatment and control groups post1 (p=0,000) and Post2 (p=0,000). The practical variables did not differ significantly between the treatment and control groups before the intervention (p=0.921).In the treatment group between pre and post1 there was a significant difference (p=0.046).Between pre and post2 (p=0.157),there was no significant difference. In the control group there was no significant difference between pre and post1 (p= 0.157) and post2 (p=0.564).After the intervention there were no significant differences in the treatment and control groups at post1 (p=0.557) as well as post2 (p=0.583). The conclusion was booklet mentoring significantly increased the knowledge and practice in of mothers in determining the nutritional status of toddlers.There is no effect of practice after post2.